Integrative analysis of mRNA and miRNA expression profiles and somatic variants in oxysterol signaling in early-stage luminal breast cancer - Holý, Petr; Brynychová, Veronika; Šeborová, Karolína; Haničinec, Vojtěch; Koževnikovová, Renata; Trnková, Markéta; Vrána, David; Gatěk, Jiří; Kopečková, Kateřina; Mrhalová, Marcela; Souček, Pavel (Molecular oncology, 2023)
Oxysterols, oxidized derivatives of cholesterol, act in breast cancer (BC) as selective estrogen receptor modulators and affect cholesterol homeostasis, drug transport, nuclear and cell receptors, and other signaling proteins. Using data from three highly overlapping sets of patients (N = 162 in total) with early-stage estrogen-receptor-positive luminal BC-high-coverage targeted DNA sequencing (113 genes), mRNA sequencing, and full micro-RNA (miRNA) transcriptome microarrays-we describe complex oxysterol-related interaction (correlation) networks, with validation in public datasets (n = 538) and 11 databases. The ESR1-CH25H-INSIG1-ABCA9 axis was the most prominent, interconnected through miR-125b-5p, miR-99a-5p, miR-100-5p, miR-143-3p, miR-199b-5p, miR-376a-3p, and miR-376c-3p. Mutations in SC5D, CYP46A1, and its functionally linked gene set were associated with multiple differentially expressed oxysterol-related genes. STARD5 was upregulated in patients with positive lymph node status. High expression of hsa-miR-19b-3p was weakly associated with poor survival. This is the first study of oxysterol-related genes in BC that combines DNA, mRNA, and miRNA multiomics with detailed clinical data. Future studies should provide links between intratumoral oxysterol signaling depicted here, circulating oxysterol levels, and therapy outcomes, enabling eventual clinical exploitation of present findings.
Keywords: nádory prsu; Transcriptome; Female; mikro RNA; Breast Neoplasms; RNA, Messenger; oxysteroly; Humans; ženské pohlaví; messenger RNA; lidé; Oxysterols; transkriptom; MicroRNAs